Progress in the Pathogenesis, Diagnosis, and Treatment of TSH-Secreting Pituitary Neuroendocrine Tumor - Luo, Peiqiong; Zhang, Lin; Yang, Lidan; An, Zhenmei; Tan, Huiwen (Frontiers in Endocrinology, 2020)
Thyroid-stimulating hormone (TSH) pituitary adenoma is one cause of central hyperthyroidism. The incidence of TSH-secreting pituitary adenoma is far lower than that of other pituitary adenomas. The clinical manifestations of TSH tumors mainly include thyrotoxicosis or thyroid goiter,increased or decreased secretion of other anterior pituitary hormones and occupying effect on the pituitary gland and its surrounding tissues.The application of high-sensitivity TSH detection methods contributes to the early diagnosis and treatment of TSH pituitary adenoma. Improvements in magnetic resonance imaging have advanced the noninvasive visualization of smaller pituitary adenomas. Treatments for TSH adenoma include surgery, drugs and radiotherapy. This review focuses on the pathogenesis, diagnosis and treatment of pituitary TSH adenoma in order to provide more information for the clinician.